Bone Cells Dynamics during Peri-Implantitis: a Theoretical Analysis - Maria Helena Fernandes; Pedro de Sousa Gomes (eJournal of Oral Maxillofacial Research)
Objectives: The present manuscript aims a detailed characterization of the bone cells dynamics during physiological bone remodelling and, subsequently, to address the cellular and molecular mechanisms that play a fundamental role in the immune-inflammatory-induced uncoupled bone remodelling observed in peri-implantitis.